EHDA Spraying: A Multi-Material Nano-Engineering Route - Haj-Ahmad, Rita; Rasekh, Manoochehr; Nazari, Kazem; Li, Yongyang; Fu, Yike; Li, Binbin; Ahmad, Zeeshan (Bentham Science Publ Ltd, 2015)
Electrohydrodynamic atomization (EHDA) enabling platform technologies have gathered significant momentum over the last two decades. Utilisation of the underpinning jetting process in tandem with desired materials (including polymers, ceramics, metals and even naturally occurring compounds such as peptides, DNA and cells) provides the basis for novel engineered therapies. Through EHDA processes, the generation of a variety of nano-meter and micro-meter scaled structures with control on surface and encapsulation features is attainable in a single step. While a host of adaptable EHDA techniques have evolved (e.g. printing and template patterning), there are two main processes that continue to dominate: electrospraying (ESy) and electrospinning (ESp). Although ESp has drawn considerable researcher interest for nanofibre applications, ESy is an important and timely process for nano-and micro-particle fabrication. Thus, an appropriate evaluation of ESy is vital. This short review focuses on key developments in the ESy field in relation to nanotechnologies with potential healthcare applications using metals, polymers and ceramics. An insight into the process of particle formation (during EHDA spraying or ESy), process parameters and materials specifications, is provided. Emerging biomedical and other healthcare research through nanotechnologies are highlighted
Keywords: Biomedical; drug delivery; electrospray; EHDA; electrospin; nanoparticles